ANALISIS PERAN GURU DALAM MEMBENTUK KARAKTER PEDULI SOSIAL SISWA MELALUI PROGRAM SEKOLAH RAMAH ANAK DI SD NEGERI 59 PEKANBARU - Yulianti; Muhamad Nukman (STKIP Subang, 2025)
Students' socially conscious character has begun to decline, as seen from their indifference to the environment, reluctance to help friends, frequent conflicts between students, and lack of communication with teachers. The purpose of this study is to determine the importance of teachers' roles in shaping students' socially conscious character in elementary schools through the Child-Friendly School Program. This research method uses qualitative research with a case study approach. This study used three stages of data collection, namely through observation, interviews, and documentation. The results of the study indicate that teachers' efforts in instilling socially conscious character are very significant. Teachers play a role as educators who provide role models, as instructors who design effective learning, as trainers through practical activities such as mutual cooperation, and as motivators who foster noble morals and caring. The implementation of Child-Friendly Schools is seen from a conducive learning environment, the application of the principles of equality, balance, freedom, and solidarity, and the involvement of students in various activities supported by adequate infrastructure. However, its implementation still faces obstacles such as limited teacher competence, lack of student focus, and the influence of the environment outside the school, so that continuous strengthening and collaboration are needed for more optimal results.